Dampak Bullying terhadap Psikologis Remaja di Kecamatan Rangkasbitung - Choirunnisa, Choirunnisa; Kudus, Wahid Abdul (Lembaga Yasin AlSys, 2022)
Bullying can be referred to as an act of violence where in this day and age there are many acts of bullying against school children, both elementary, junior high and even high school / vocational school. By knowing deviant behavior or morals that are not good in themselves, including teenagers, it can make teachers or parents think that they have failed in educating the individual's behavior, because bullying can be caused by the behavior of someone who thinks he has power among others so that he will be arbitrary to weak individuals. However, the forms of bullying are different, not only physically but also verbally, where the words that are uttered as if they think they are just a joke can actually bring down the spirit of someone they are ridiculing. So that the impact of bullying felt by these students is very diverse due to one factor and another, especially in Rangkasbitung District itself which has diversity in each individual school child. This research method uses a qualitative descriptive method by collecting data through the interview and observation process. The results of this study are (1) the forms of bullying, (2) the factors that cause bullying, (3) the psychological impact of adolescents due to bullying and, (4) how to prevent and overcome bullying.